Rancang Bangun Sistem Elektroplating Otomatis Berbasis Teknologi Android - Adriyasa, I Kadek Ricky; Santhiarsa, I G.N. Nitya; Kusuma, I G.B. Wijaya (Teknik Desain Mekanika, 2021)
Abstract This study seeks to help conventional entrepreneurs in Bali develop technology with digital automation technology, so that the metal plating process can be controlled more easily simultaneously without being constrained by distance. This research is also to find out the control system on the electroplating process tool functions or is connected to a laptop and android smartphone via the internet, to connect an android smartphone and a laptop during the electroplating process this research uses the Blynk application, Arduino programming, the MCU ESP 8266 Node Tool. In the electroplating process with the control system, two tests were carried out with specimen I and specimen II, which resulted in the weight of the specimen using two scales, namely analytical scales and digital scales. From these scales, the results are almost the same as the analytical balance for specimen I without control, showing the results of 2.8861g. This result is close to the result of the digital scale, which is 2.89g, for the analytical balance of specimen II, which is 3.3009g, this result is closer to the digital scale, which is 3, 26g and for specimen I with control, the result is 2.9444g, this result is the same as the digital scale, which is 2.94g, while for specimen II, the result is 3.4238g, this result is close to the digital scale, which is 3.50g. Keywords: Electoplating, Control System, Android Smartphone